Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) dalam Meningkatkan Kesejahteraan Masyarakat di Kabupaten Pandeglang (Studi di Desa Ciherang Kecamatan Picung Kabupaten Pandeglang) - Iyan Robiansyah; Nana Suryapermana; Budi Sudrajat (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2022)
This thesis discusses the Implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) in Improving the Social Welfare of the Community in Pandeglang Regency which has the aim of fulfilling the right of citizens to a decent place to live in a healthy, safe, comfortable and orderly environment. The issues and objectives discussed in this thesis is about all the Policy, Implementation, Problems and Efforts to Overcome Problems and Results in implementing of the BSPS Program in Ciherang Village. The location of this study is in Ciherang Village, Picung District, Pandeglang Regency, this research is to use a descriptive field research method with qualitative analysis, meaning that the researcher describes the reality in the field correctly. This research instrument is a researcher as a human instrument using interview guidelines and documentation. Observational data collection techniques, interviews and documentation. The data obtained are then analyzed continuously by reducing data, verifying data and testing data sensitivity. The results showed that the implementation of the BSPS Program in Ciherang Village, the community has felt the benefits, with the type of assistance for Improving the Quality of Independent Houses whose Assistance Value is Rp. 17,500,000 which is distributed through their respective accounts to buy building materials worth Rp. 15,000,000 and artisan wages worth Rp. 2,500,000. beneficiaries are required to have self-help sourced from their families, communities, governments and others. Keywords: Self-Help Housing Stimulant Assistance Program, Community Empowerment, Community Welfare.